Practical WPF Charts and Graphics Advanced Chart and Graphics Programming with the Windows Presentation Foundation - Xu, Jack.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Creating 2D and 3D charts is one of the most common uses of computer graphics. Such charts can have wide applications in representing mathematical, physical, and economic functions in your daily life. Whether you are an engineer, a quantitative analyst, a teacher, or a student, you will end up dealing with charting applications to some degree. Windows Presentation Foundation (WPF) is a next-generation graphics platform that enables you to build advanced user interfaces incorporating documents, media, 2D and 3D graphics, and animations. It is an ideal development tool that allows you to not only generate data, but also easily represent data graphically. Practical WPF Charts and Graphics provides all the tools you will need to develop professional chart and graphics applications in WPF and C#. This book will be useful for WPF and C# programmers of all skill levels, providing a complete and comprehensive explanation of WPF$1 (Bs graphics capability and the creation of various charts, and paying special attention to the details of code implementation.s
Overview of WPF Programming -- 2D Transformations -- WPF Graphics Basics in 2D -- Colors and Brushes -- 2D Line charts -- Specialized 2D Charts -- Stock Charts -- Interactive 2D Charts -- 2D Chart Controls -- Data Interpolations -- Curve Fitting -- 3D Transformations -- WPF Graphics Basics in 3D -- 3D Charts with the WPF 3D Engine -- 3D Charts Without the WPF 3D Engine -- Specialized 3D Charts.
Keywords: Computer science; Computer Science; Programming Techniques